Physiological Plasticity Is Important for Maintaining Sugarcane Growth under Water Deficit - Marchiori, Paulo E. R.; Machado, Eduardo C.; Sales, Cristina R. G.; Espinoza-Núñez, Erick; Magalhães Filho, José R.; Souza, Gustavo M.; Pires, Regina C. M.; Ribeiro, Rafael V. (Frontiers in Plant Science, 2017)
The water availability at early phenological stages is critical for crop establishment and sugarcane varieties show differential performance under drought. Herein, we evaluated the relative importance of morphological and physiological plasticity of young sugarcane plants grown under water deficit, testing the hypothesis that high phenotypic plasticity is associated with drought tolerance. IACSP95-5000 is a high yielding genotype and IACSP94-2094 has good performance under water limiting environments. Plants were grown in rhizotrons for 35 days under three water availabilities: high (soil water matric potential [Ψm] higher than 20 kPa); intermediate (Ψm reached -65 and -90 kPa at the end of experimental period) and low (Ψm reached values lower than -150 kPa). Our data revealed that morphological and physiological responses of sugarcane to drought are dependent on genotype and intensity of water deficit. In general, IACSP95-5000 showed higher physiological plasticity given by leaf gas exchange and photochemical traits, whereas IACSP94-2094 showed higher morphological plasticity determined by changes in leaf area and specific leaf area. As IACSP94-2094 accumulated lesser biomass than IACSP95-5000 under varying water availability, it is suggested that high morphological plasticity does not always represent an effective advantage to maintain plant growth under water deficit. In addition, our results revealed that sugarcane varieties face water deficit using distinct strategies based on physiological or morphological changes. When the effectiveness of those changes in maintaining plant growth under low water availability is taken into account, our results indicate that the physiological plasticity is more important than the morphological one in young sugarcane plants.